Assessing extent of building damage following an earthquake: case study of the 2023 Turkey-Syria doublet - Guan Chen; Yong Liu; Zhangfeng Ma; Jiashu Yang; Michael Beer; Siau Chen Chian; Shengji Wei (npj Natural Hazards, 2025)
Abstract An earthquake doublet (M w 7.8 and M w 7.5) struck southeastern Turkey on February 6, 2023, causing widespread devastation. To evaluate seismic damage across 11 provinces, we analysed strong motion data, developed fragility functions and building damage state maps, validated by official reports and field surveys. Using five idealized structural models with varying fundamental periods, we estimated damage states for typical Turkish structures. The damage maps highlight how building period interacts with strong motion, providing valuable references for rapid assessment of building damage states and damaging potential of ground motions to various structures. Moreover, near-fault damage was significantly underestimated by seismic hazard maps based on empirical ground motion models, as observed ground motion intensities significantly exceeded predictions at R J B less than 10 km. Additional phenomena associated with fault rupture, such as pulse-like ground velocities, surface fault displacements, and geohazards, further amplified damage. This study offers critical insights into near-fault seismic damage mechanisms and emphasizes the need for special tailored ground motion models for seismic hazard and risk assessment to enhance community resilience.